2014
DOI: 10.1590/s1984-29612014018
|View full text |Cite
|
Sign up to set email alerts
|

Dioctophyme renale Goeze, 1782 in a cat with a supernumerary kidney

Abstract: This study reports a case of parasitism by Dioctophyme renale in a supernumerary kidney and abdominal cavity of a female cat in Brazil. The three-year-old cat of indeterminate breed presented abdominal distension and was taken to the University of Contestado Veterinary Hospital in Canoinhas, state of Santa Catarina, since the owner suspected pregnancy. An ultrasound scan did not confirm pregnancy but revealed parasitism in the kidney. This case is worth reporting because domestic cats are rarely hosts of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 6 publications
1
6
0
10
Order By: Relevance
“…In this study, three cats were diagnosed with dioctophymosis, which corroborates with the literature that cites the low frequency of parasitism in this species, with only two reports in cats (VEROCAI et al, 2009;PEDRASSANI et al, 2014). In contrast, several cases of canine dioctophymosis have been reported in Brazil (COLPO et al, 2007;MESQUITA et al, 2014;RAHAL et al, 2014), but few studies have discussed the factors that might be involved in maintaining the parasitosis.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, three cats were diagnosed with dioctophymosis, which corroborates with the literature that cites the low frequency of parasitism in this species, with only two reports in cats (VEROCAI et al, 2009;PEDRASSANI et al, 2014). In contrast, several cases of canine dioctophymosis have been reported in Brazil (COLPO et al, 2007;MESQUITA et al, 2014;RAHAL et al, 2014), but few studies have discussed the factors that might be involved in maintaining the parasitosis.…”
Section: Introductionsupporting
confidence: 89%
“…Infection in cats has been reported less frequently, with reports in Rio de Janeiro and Santa Catarina (VEROCAI et al, 2009;PEDRASSANI et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has a complex life cycle that requires an aquatic oligochete or annelid as an intermediate host with fishes and frogs being paratenic hosts . It is distributed worldwide with most cases in dogs, cats, and wild animals reported in the neotropics, especially in Brazil, where the frog Chaunus ictericus is a known paratenic host of D renale …”
Section: Introductionmentioning
confidence: 99%
“…Adult D. renale, the so-called "giant kidney worm", varies in size according to the number of the parasites present and the particular host infiltrated (Mehlhorn, 1993). Although, the parasite's natural hosts are the mustelids (Fyvie, 1971;Measures, 2001;Mech and Tracy, 2001) and ichthyophagous carnivores (Acosta et al, 2008;Ribeiro et al, 2009;Verocai et al, 2009), the nematode has been found in a great variety of carnivores, herbivores and omnivores as well as in man (Vladimova et al, 2002;Urano et al, 2001, Measures, 2001Sardjono et al, 2008;Ishizaki et al, 2010;Tokiwa et al, 2011;Katafigiotis et al, 2013;Pedrassani et al, 2014;Yang et al, 2016;Norouzi et al, 2017). In the mustelids, an extrarenal localization is rare, whereas in canines asymptomatic cases of dioctophymosis have been described with both renal and extrarenal parasite locations, as evidenced during surgery or necropsy (Pereira et al, 2006;Ferreira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%